Benetton’s (In)Equality: A Semiotic Reading - Muljadi, Hianly; Angjaya, Sonny; Deborah, Joanna (Paradigma: Jurnal Kajian Budaya, 2022)
United Colors of Benetton, or UCB, has been using its advertisements to deliver positive messages and values that the clothing company represents. This article analyzes one of the photographs in Benetton’s campaign for their Spring Summer Collection of 2018. The campaign, which consists of some photographs by Oliviero Toscani, raises the theme of equality of gender and ethnicity. It shows various photographs of both female and male models from different ethnicities. However, it is found that there is one photograph that shows inconsistency with the very value that Benetton wants to convey through their campaign. Based on the semiotic analysis, the study shows that the photograph can be read as having an entirely different message that the company intends to voice. This article proves that multiple interpretations can be applied to a text, and a text can betray itself.